HERMETIZATION ABILITY ANALYSIS OF RUBBER SEALS OF TEST PACKERS IN THE FRAMEWORK OF CAE-SYSTEMS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The problems of test process of wellhead and preventer equipment during theconstruction and underground repair of wells are considered. The effects of extrusion of sealmaterial into the gap to hermetization ability of self-sealing packer and quality test ofwellhead and preventer equipment as a whole was analyzed and the need for serious researchof self-sealing rubber cuffs was justified. The conditions of application of the model physics ofthemooney-rivlin material behavior in the implementation of computer simulation of stressstrainstate of a rubber self-sealing cuff are analyzed. The major operational factorsinfluencing the ability hermetization of self-sealing cuff during the test are described. Thestages and results of computer simulation of stress-strain state of self-sealing rubber cuffstaking into account operational factors were determined. Comparison of the research results ofhermetization ability cuff in the quantitative simulation and experimental study was done.Keywords: wellhead test packer, self-sealing cuffs; computer simulation, stress-strainedstate.